Expression of the small regulatory RNA gene mmgR is regulated negatively by AniA and positively by NtrC in Sinorhizobium meliloti 2011 - Ceizel Borella, German (2017)
In the N2-fixing symbiont of alfalfa root nodules, Sinorhizobium meliloti 2011, the mmgR gene encodes a 77 nt small untranslated RNA (sRNA) that negatively regulates the accumulation of polyhydroxybutyrate (PHB) when the bacterium is grown under conditions of surplus carbon (C) in relation to nitrogen (N). We previously showed that the expression of mmgR is primarily controlled at the transcriptional level and that it depends on the cellular N status, although the regulatory mechanism and the factors involved were unknown. In this study, we provide experimental data supporting that: (a) mmgR is induced upon N limitation with the maximum expression found at the highest tested C/N molar ratio in the growth medium; (b) a conserved heptamer TTGTGCA located between the −35 and −10 mmgR promoter elements is necessary and sufficient for induction by N limitation; (c) induction of mmgR requires the N-status regulator NtrC; (d) under C limitation, mmgR transcription is repressed by AniA, a global regulator of C flow; (e) the mmgR promoter contains a conserved dyadic motif (TGC[N3]GCA) partially overlapping the heptamer TTGTGCA, which was also found in the promoters of the PHB-related genes phaP1, phaP2, phaZ and phaR (aniA) of S. meliloti and other alpha-proteobacteria. Taken together, these results suggest that the mmgR promoter would integrate signals from the metabolism of C and N through – at least – the global regulators NtrC and AniA, to provide an optimal level of the MmgR sRNA to fine-tune gene expression post-transcriptionally according to varying C and N availability.